The Role of the Principal’s Leadership in Enhancing Teacher Professionalism at SMK Negeri 4 Bandar Lampung: A Qualitative Study - Safira, Nurul; Alamsyah, Yosep Aspat (Cultura Islamica: Journal of Islamic Studies, Management, and Culture, 2025)
Teacher professionalism is a crucial factor in improving the overall quality of education. The school principal plays a pivotal role in fostering this professionalism by motivating, guiding, and acting as a role model for teachers in areas such as instructional practices, professional development, and the integration of technology. This study aims to analyze the leadership practices of the principal in enhancing teacher professionalism at SMK Negeri 4 Bandar Lampung. Using a descriptive qualitative approach, data were gathered through interviews, observations, and document analysis. The research subjects included the principal, vice principal of curriculum, department heads, and selected teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing, with validation ensured via triangulation of techniques and sources. The findings indicate that the principal enhances teacher professionalism in three key ways: (1) motivating teachers through personal example, structured support, and motivational strategies; (2) implementing continuous development programs, such as in-house training, academic supervision, teacher internships, and collaboration through teacher working groups; and (3) serving as a role model in professionalism, discipline, work ethic, and in fostering a religious and positive school culture. Additionally, the principal demonstrates strong communication skills and active participation in professional organizations. This study concludes that proactive, inspirational, and communicative leadership significantly contributes to the development of teacher professionalism in vocational school settings.